LESSONS LEARNT FOR THE INDONESIAN MILITARY LEADERS FROM GENERAL PERICLES’ STRATEGIC-TRANSFORMATIVE LEADERSHIP - Wibawanto Nugroho Widodo (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2020)
For a nation to be great, such a nation shall have great and professional military leaders which are contextual to the time and social context of their nation. That is why Indonesian military leaders need to take some lesson-learned from historical records of great military leaders, one of them is the strategic and transformative leadership of General Pericles, an Athenian General.  Therefore, this article analyzes about Pericles’ great leadership, especially in what ways and how to measure it. The data corpus of this study is “The Landmark Thucydides: A Comprehensive Guide to the Peloponnesian War” by Thucydides. The research uses qualitative study and critical review on related archival documentation. All data collected is validated by cross-checking with other credible open sources about the life and leadership records of General Pericles. The qualitative analysis uses to examine three main variables that are critical to his strategic-transformative leadership: his grand strategy (strategic mindset); his dedication to the highest level of life for Athenian citizens (altruistic mindset and heart); and his statesmanship, generalship, leadership (his leadership traits). The main International Relations theories used for examining General Pericles’s leadership are the theory of realism and institutionalism coupled with personality analysis of General Pericles himself. This article lays out the answer to the two thesis questions. This article proves that as a realist and visionary leader, Pericles’s leadership was central to the Athenian greatness in terms of its political, social, demographic, and military affairs, that successfully brought his nation to the global height. Putting in the current Indonesian context, this strategic-transformative leadership is important for any Indonesian military leaders to possess since any great nations shall have great and professional military leaders which are contextual to the time and social context of their nation.